Poroplastic analysis of concrete dams and their foundations using ABAQUS - Sinske, A. N.(Alexander Nicholas) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1996.